CORRELATION BETWEEN CLUSTER OF DIFFERENTIATION 4 (CD4) WITH RADIOLOGICAL FEATURES OF TB-HIV PATIENS - Angiesta Pinakesty (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2022)
ABSTRACT Background: Tuberculosis (TB) is an opportunistic infection the most often found in Human Immunodeficiency Virus (HIV) infection and is the leading cause of death among Orang Dengan HIV / AIDS (ODHA). The risk of TB transmission is 26 to 31 times greater in people with HIV than people without HIV. TB-HIV patients tend to have negative acid-resistant bacteria (AFB) laboratory tests and atypical radiological images. Both of these become obstacles in determining the diagnosis and management. The heavier level of immunosuppression in TB-HIV patients as indicated by a decrease in the level of cluster of differentiation 4 (CD4), the less characteristic the radiological picture was. CD4 count is associated with clinical manifestations of HIV patients that can be seen from radiological images, so that it can be used in accelerating diagnosis and management of TB-HIV. This study aims to determine the relationship between CD4 and the radiological picture of TB-HIV patients at PKU Muhammadiyah Hospital of Surakarta. Methods: This study used a cross sectional research design and was conducted from November to December 2020 at the PKU Muhammadiyah Hospital of Surakarta. The number of research subjects as many as 30 patients who were taken with a non-probability purposive sampling technique. Retrieval of data using patient medical record data. Data were analyzed using Fisher's exact test. Results: Fisher's exact test showed no association between CD4 cell count and radiological features of TB-HIV patients (p = 1,000). Conclusion: There is no significant association between CD4 cell count and radiological features of TB-HIV patients.